Comparison of Online Shopping Behavior Before and During Pandemic towards Generation Z - Rino Febrianno Boer; Reina Amerya Ayu; Fatima Alifha (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The increasing adoption of digital platforms has significantly influenced consumer behavior, particularly among Generation Z, necessitating a deeper understanding of how external crises reshape purchasing patterns. Grounded in consumer behavior theories, this study explores how key factors such as quality consciousness, green consumer value, materialism, and impulsive buying influence Generation Z's decision-making styles—extensive, limited, and habitual—before and during the COVID-19 pandemic. The primary objective is to uncover the extent to which these factors evolved during the pandemic and their implications for communication strategies in digital marketing. Using a Partial Least Squares - Multi-Group Analysis (PLS-MGA) framework, the study employs a quantitative approach with data collected from Generation Z respondents across two time periods: pre-pandemic (2018, n=130) and mid-pandemic (2022, n=250). The analysis evaluates the relationships between variables and compares changes over time to identify significant shifts in consumer priorities. Results reveal that external global events amplify internal consumer values, with quality consciousness and green consumer value becoming more pronounced during the pandemic. Additionally, materialism and impulsive buying gained significance across all decision-making styles, highlighting the psychological impact of the crisis. These findings contribute to the field of communication by emphasizing the need for brands to adapt their messaging to reflect evolving consumer priorities, particularly in times of uncertainty. This research underscores the role of communication in fostering trust and aligning with sustainable and quality-driven values, offering actionable insights for marketers targeting Generation Z.